2021
DOI: 10.1002/oby.23292
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in primary care: A pooled analysis of two pragmatic cluster‐randomized trials

Abstract: ObjectiveThe aim of this study was to report the results of five weight‐loss interventions in primary care settings in underserved patients and to compare the level of pragmatism across the interventions using the Pragmatic Explanatory Continuum Indicator Summary (PRECIS‐2) tool.MethodsData from 54 primary care clinics (2,210 patients) were pooled from the Promoting Successful Weight Loss in Primary Care in Louisiana (PROPEL) and Rural Engagement in Primary Care for Optimizing Weight Reduction (REPOWER) cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…12,20 With structures and supports in place, patients are achieving weight loss outcomes that have potential to slow the public health trends toward increasing obesity and the resulting comorbid conditions. [21][22][23][24][25][26] Understanding more about what motivates primary care practice members toward providing obesity care and what steps could be taken to overcome perceived barriers is needed. This study reports on a survey completed by practice members at 18 diverse primary care practices in Colorado regarding their perceptions of the importance of obesity care in their practice, what services are currently provided, satisfaction with the care provided, challenges with providing obesity care, and interests in overcoming these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…12,20 With structures and supports in place, patients are achieving weight loss outcomes that have potential to slow the public health trends toward increasing obesity and the resulting comorbid conditions. [21][22][23][24][25][26] Understanding more about what motivates primary care practice members toward providing obesity care and what steps could be taken to overcome perceived barriers is needed. This study reports on a survey completed by practice members at 18 diverse primary care practices in Colorado regarding their perceptions of the importance of obesity care in their practice, what services are currently provided, satisfaction with the care provided, challenges with providing obesity care, and interests in overcoming these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this contention, two recent pragmatic trials demonstrated that weight loss approaches conducted in primary care settings are feasible and effective ( 6 , 7 ). While these trials were conducted in the context of primary care, data collection was conducted using a “gold standard” approach by having trained research technicians measure the outcomes at fixed intervals ( 8 ). Recently, there has been increasing interest in collecting outcome data in pragmatic trials conducted in healthcare settings from existing electronic medical record (EMR) platforms ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%